Rethinking finance in the face of new challenges - Bourghelle, David; Pérez, Roland; Rozin, Philippe (Critical studies on corporate responsibility, governance and sustainability ;, 2021)
Rethinking Finance in the Face of New Challenges provides an overview of the new research perspectives devoted to financial activity, reconsidering the opposition between orthodox and heterodox schools of finance. The purpose is to identify new theoretical and practical issues around the concepts of values, radical uncertainty, and financial instability, but also to examine the consequences of the financialisation process on the dynamics of organisations and markets, as well as on value production mechanisms. This fifteenth volume of Critical Studies on Corporate Responsibility, Governance and Sustainability begins by exploring the globalisation and financialisation of economies, central banks and corporate strategies before switching to focus on financial value as a historically situated social construct. The book then examines the relationship between finance, social value and sustainable development and presents several avenues for reflection with a view to a paradigmatic renewal of research and teaching in finance. At a time when an unprecedented infectious and sanitary crisis is generating disastrous financial, economic, social and societal repercussions, the work presented in this book will stimulate reflection and contribute to the renewal of a Finance that now has to face many new social, societal and environmental challenges.